2020
DOI: 10.1016/j.cub.2020.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Ras and Rac Activity Shapes Macropinocytic Cups and Enables Phagocytosis of Geometrically Diverse Bacteria

Abstract: Highlights d We identify a new regulator that shapes macropinocytic and phagocytic cups d Shaping protrusions into cups requires differential regulation of Ras and Rac d Cups are organized by integrating interactions with phospholipids and multiple GTPases d Defective cup formation causes a target shape-specific defect in phagocytosis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 69 publications
(100 reference statements)
0
48
0
Order By: Relevance
“…Evidence suggests that phagocytosis of differently shaped particles requires different signaling cascades. Experiments with the amoeba Dictyostelium showed that the coordinated activity of the small-GTPases Rac and Ras at the phagocytic cup by the multidomain protein RGBARG (RCC1, RhoGEF, BAR, and RasGAP-containing protein) is key for uptake of particles and microbes of different shapes ( 87 ). The authors propose that RGBARG promotes the protrusion of the cytoskeleton at the periphery of the phagocytic cup by expanding Rac activation in this region, while it suppresses Ras at more central regions of the nascent phagocytic cup ( 87 ).…”
Section: Model Particle Size and Shape: Experimental Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that phagocytosis of differently shaped particles requires different signaling cascades. Experiments with the amoeba Dictyostelium showed that the coordinated activity of the small-GTPases Rac and Ras at the phagocytic cup by the multidomain protein RGBARG (RCC1, RhoGEF, BAR, and RasGAP-containing protein) is key for uptake of particles and microbes of different shapes ( 87 ). The authors propose that RGBARG promotes the protrusion of the cytoskeleton at the periphery of the phagocytic cup by expanding Rac activation in this region, while it suppresses Ras at more central regions of the nascent phagocytic cup ( 87 ).…”
Section: Model Particle Size and Shape: Experimental Evidencementioning
confidence: 99%
“…Experiments with the amoeba Dictyostelium showed that the coordinated activity of the small-GTPases Rac and Ras at the phagocytic cup by the multidomain protein RGBARG (RCC1, RhoGEF, BAR, and RasGAP-containing protein) is key for uptake of particles and microbes of different shapes ( 87 ). The authors propose that RGBARG promotes the protrusion of the cytoskeleton at the periphery of the phagocytic cup by expanding Rac activation in this region, while it suppresses Ras at more central regions of the nascent phagocytic cup ( 87 ). Although Dictyostelium without RGBARG showed improved phagocytosis of larger model particles and yeast, the spatial regulation of Ras by RGBARG was found to be important for phagocytosis of elongated cargoes ( 87 ).…”
Section: Model Particle Size and Shape: Experimental Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, CARMIL-GAP’s GAP activity may contribute to phagocytosis and chemotactic streaming by regulating additional down-stream effectors of Rac1 (e.g. PAK kinases, formins, IQGAP; (Buckley et al, 2020; Rivero and Xiong, 2016)).…”
Section: Dicussionmentioning
confidence: 99%
“…Macropinocytosis is dependent on cytoskeletal remodeling at the plasma membrane to induce the formation of structures called dorsal ruffles that form the beginning of a macropinosome. Ras signaling cascades lead to activation of the Rho GTPase Rac1, initiating actin polymerization and formation of branched actin networks that provide structure for remodeling of the plasma membrane (Swanson, 2008;Fujii et al, 2013;Buckley et al, 2020). One family of proteins important for stabilizing branched actin networks are the α-actinin proteins, which are actin bundling proteins that stabilize the actin cytoskeleton in structures like lamellipodia and focal adhesions (Sjoblom et al, 2008;Murphy and Young, 2015).…”
Section: Introductionmentioning
confidence: 99%